Comparative effects of high-dose atorvastatin versus moderate-dose rosuvastatin on lipid parameters, oxidized-LDL and inflammatory markers in ST elevation myocardial infarction. Issue 2 (April 2015) - Aydin, Meryem Ulku; Aygul, Nazif; Altunkeser, Bulent Behlul; Unlu, Ali; Taner, Alpaslan
Abstract: Background: The important role of oxidized low density lipoprotein (oxidized-LDL) in preclinic atherosclerosis and pathophysiology of acute coronary syndromes studies have reported. Oxidation of LDL activates many inflammatory and atherogenic pathways and plays a pivotal role in atherosclerosis. Our aim in this study is to compare the effects of 80 mg daily dose of atorvastatin and 20 mg daily dose of rosuvastatin on lipid profiles and the levels of oxidized-LDL and inflammatory markers in ST elevation myocardial infarction (STEMI). Methods: One hundred and twenty patients with STEMI were enrolled in this study. The patients were randomly assigned to receive atorvastatin (80 mg/day) or rosuvastatin (20 mg/day) by using a ratio of 1:1 after revascularization. The levels of total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C), LDL-C, apolipoprotein B and apolipoprotein A were compared between groups after 4-week therapy. The values of oxidized-LDL, tumor necrosis factor receptor 1 and 2, Interleukin-6 and hs-CRP were also compared between groups. The Student's t test was used to detect absolute and percent changes between groups, and p < 0.05 was considered as statistically significant for all tests. Results: After treatment in both treatment groups LDL-C, oxidized-LDL, hs-CRP, tumor necrosis factor receptor 1 and 2, Interleukin-6 values significantly decreased according to baseline. The only difference was in HDL-C levels. HDL-C slightly decreased in atorvastatin group while it increased in the rosuvastatin group compared baseline (−1.4 ± 8.9 mg/dl vs 2.0 ± 9.4 mg/dl, p = 0.04). Conclusion: We reported that both statin treatment regiments have comparable effects on LDL-C, oxidized-LDL and inflammatory markers. Moreover, it was observed that rosuvastatin was more effective in terms of ability to increase HDL-C level. Based on these findings, 20 mg daily dose of rosuvastatin may be an alternative to 80 mg daily dose of atorvastatin in patients with acute coronary syndrome. Highlights: Atorvastatin was compared to rosuvastatin on ox-LDL, lipid parameters and inflammatory markers. The study was done in patient with ST elevation myocardial infarction. Both statins have comparable effects on LDL-C, ox-LDL and inflammatory markers. Rosuvastatin was more effective in terms of ability to increase HDL-C level.